Load-management applications for the industrial sector - Ashok, S; Banerjee, R (Applied energy, 2000)
The goal of any load-management program is to maintain, as nearly as possible, a constant level of load, thereby allowing the system load factor to approach 100%. The important benefits of load management are reduction in maximum demand, reduction in power loss, better equipment utilisation and saving through reduced maximum demand charges. Load shifting, one of the simplest methods of load management, is to reduce customer demand during the peak period by shifting the use of appliances and equipment to partial peak and off-peak periods. Here no loads are being switched off, but only shifted or rescheduled, and hence the total production is not affected. In this paper, a fully fledged program is developed for load shifting and the same has been tried with the actual load data collected from a typical fertiliser and chemical industry plant.